Análisis semiótico de la película Birdman (o la inesperada virtud de la ignorancia) - Núñez Alberca, Alejandro (2021)
This thesis analyzes Alejandro González Iñárritu´s film Birdman (2014) employing elements of film narratology as well as the theorical premises of the tensive hipotesis, primarily the semiotic of the event formulated by Claude Zilberberg as a critical continuation of the greimasian structural project. We postulate that (1) the distribution of intensity in the single tracking shot, (2) the incorporation of the space outside of the frame, and (3) what we have called the point-of-view-game, the film creates a discourse in which these three elements are responsible for controlling the tensive modulations, capable of operating both in the narrative and the discursive levels.